2006
DOI: 10.1051/lait:2005048
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors from bovine milk and colostrum: composition, extraction and biological activities

Abstract: -EGF, BTC, IGF-I, IGF-II, TGF-β1, TGF-β2, FGF1 and 2, and PDGF are the main growth factors present in bovine milk and colostrum. All of these growth factors are also found in human milk but at a lower concentration. The various compositional data reported in the literature vary greatly but it is evidenced that the day of lactation has the most important effect. Milk growth factors are characterized by a neutral to alkaline isoelectric point (pI) and a molecular mass between 6400 g·mol -1 and 30000 g·mol -1 . H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
85
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 211 publications
2
85
0
3
Order By: Relevance
“…Colostrum and milk, but especially colostrum, are also rich sources of a suite of compounds such as growth factors, hormones, cells, and antimicrobial factors, including lactoferrin, lysozyme, lactoperoxidase, and cytokines (e.g., IL-1β, IL-6, TNF-α, IFN-γ, and IL-1ra), which in one way or another are involved in the stimulation and regulation of the growth and development of the GIT in this period (e.g., Burrin et al, 1995;Donovan and Odle, 1994;Xu, 1996;Sangild et al, 2000;Xu et al, 2000;Odle et al, 1996;Gauthier et al, 2006;Boudry et al, 2008). It is outside the scope of this review to discuss each (isolated) growth factor/ compound and its effects on the structure and function of the GIT for young pigs; however, interest has focused particularly on the properties and roles of epidermal growth factor (EGF), the insulin-like growth factors, insulin, and other compounds such as transforming growth factor.…”
Section: Growth Factors In Colostrum and Milkmentioning
confidence: 99%
“…Colostrum and milk, but especially colostrum, are also rich sources of a suite of compounds such as growth factors, hormones, cells, and antimicrobial factors, including lactoferrin, lysozyme, lactoperoxidase, and cytokines (e.g., IL-1β, IL-6, TNF-α, IFN-γ, and IL-1ra), which in one way or another are involved in the stimulation and regulation of the growth and development of the GIT in this period (e.g., Burrin et al, 1995;Donovan and Odle, 1994;Xu, 1996;Sangild et al, 2000;Xu et al, 2000;Odle et al, 1996;Gauthier et al, 2006;Boudry et al, 2008). It is outside the scope of this review to discuss each (isolated) growth factor/ compound and its effects on the structure and function of the GIT for young pigs; however, interest has focused particularly on the properties and roles of epidermal growth factor (EGF), the insulin-like growth factors, insulin, and other compounds such as transforming growth factor.…”
Section: Growth Factors In Colostrum and Milkmentioning
confidence: 99%
“…Transforming growth factor-␤2 (TGF-␤2) is a multifunctional growth factor that is present in both human (ϳ0.1-5.3 ng/ml) and bovine (ϳ13-1,150 ng/ml) milk as the most dominant isoform of the TGF-␤ family (2,8). TGF-␤s have been reported to exert various functions in the gut in vivo, such as immunomodulation (30), regulation of intestinal cell proliferation and differentiation (9,40), and protection against intestinal injury in a NEC-like model (19).…”
mentioning
confidence: 99%
“…Besides having low bacterial content (3,4), physiologic osmolality (230-270 mOsm/kg) and neutral pH (6.5-6.8), it provides the cells with nutrients (3) and growth factors (12,13). Although there has been some controversy (6,8), it has been suggested that milk with a lower fat content might be more appropriate to maintain PDLF viability than milk with a higher fat content (14).…”
Section: Introductionmentioning
confidence: 99%